1999
DOI: 10.1080/01904169909365695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc on the alleviation of boron toxicity in tomato

Abstract: A greenhouse experiment involving four levels of boron (0, 5, 10 and 20 mg B kg -1 ) and the levels of zinc (0, 10 and 20 mg Zn kg -1 ) was conducted in tomato plants (Lycopersicon esculentum L., cv., 'Lale'). Boron toxicity symptoms occurred at 10 to 20 mg kg -1 B levels. These symptoms were somewhat lower in the plants grown with applied Zn. Fresh and dry weights of the plants clearly decreased with applied B. However Zn treatments partially depressed the inhibitory effect of B on the growth. Increased level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…Increasing B levels in the NS significantly boosted the B content in edible parts of purslane (Figure 2) with no differences in yield and DW (Table 1). Our results are in agreement with several authors [34][35][36][37][38][39], who reported significant increases of B in different species as a consequence of high concentrations of this element in growing media and/or NS. In fact, B moves from the roots with the transpiration stream and accumulates in growing points of leaves and stems [40].…”
Section: Discussionsupporting
confidence: 94%
“…Increasing B levels in the NS significantly boosted the B content in edible parts of purslane (Figure 2) with no differences in yield and DW (Table 1). Our results are in agreement with several authors [34][35][36][37][38][39], who reported significant increases of B in different species as a consequence of high concentrations of this element in growing media and/or NS. In fact, B moves from the roots with the transpiration stream and accumulates in growing points of leaves and stems [40].…”
Section: Discussionsupporting
confidence: 94%
“…In this study, shoot-root fresh and dry weight showed an alteration according to boron dose and soil type during boron stress and decreased compared to control plants. A similar result has been reported in corn (Güneş et al, 2000a), tomato (Güneş et al, 2000b), potato (Ayvaz, 2009), purslane plants (Samet and Çakılı, 2016;2019) for shoot fresh weight, in pepper (Akıncı, 2006;Eraslan et al, 2007), corn (Palta and Gezgin, 2011), canola (Koohkan and Maftoun, 2016; purslane plants (Samet and Çakılı, 2016;2019) and buckwheat plant (Yazıcı and Korkmaz, 2020) for shoot dry weight.…”
Section: The Effect Of B On Plant Shoot-root Fresh and Dry Weightssupporting
confidence: 77%
“…However, in the present study, the close relation between Zn efficiency and B tolerance could not be explained by the differences in B concentration in shoots. Also Grewal et al (28) in oilseed rape and Günes et al (29) in tomato showed increases in B concentration in shoots under Zn deficiency, but these increases in B concentration in Zn-deficient plants were attributable to a concentration effect due to reduced growth, rather than the 1826 TORUN ET AL. On average of 25 wheat cultivars, Zn fertilization tended to increase B concentration in the shoot.…”
Section: Discussionmentioning
confidence: 98%